2019
DOI: 10.1055/s-0039-1697617
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Primary Biliary Cholangitis: A Comprehensive Review

Abstract: Primary biliary cholangitis (PBC) is a chronic cholestatic liver disease characterized by autoimmune destruction of small to medium size intrahepatic bile ducts. The etiology of PBC remains unknown and pathogenesis features immune-mediated biliary injury, alongside the consequences of chronic cholestasis. PBC is strongly associated with the loss of immune tolerance against mitochondrial antigens and the subsequent presence of an articulated immunologic response that involves both humoral and cellular responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 225 publications
(211 reference statements)
5
84
0
Order By: Relevance
“…Criteria. Studies were included if they met the following criteria: (1) the study was original research; (2) the study reported a prevalence or incidence (or it reported raw data that allowed the calculation of estimates); (3) the study was conducted in Europe; and (4) the study was published in 2000 or later.…”
Section: Inclusion and Exclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Criteria. Studies were included if they met the following criteria: (1) the study was original research; (2) the study reported a prevalence or incidence (or it reported raw data that allowed the calculation of estimates); (3) the study was conducted in Europe; and (4) the study was published in 2000 or later.…”
Section: Inclusion and Exclusionmentioning
confidence: 99%
“…Exclusion criteria for the meta-analysis were as follows: (1) the study was a review article; (2) the study was a genome study or an animal study; (3) the study described the epidemiology of PBC among hospitalized patients; and (4) the study did not specifically describe patients with PBC.…”
Section: Inclusion and Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease characterized by nonsuppurative inflammatory destruction of the interlobular bile ducts [ 143 ]. It is well established that cholestasis causes Cu accumulation in the liver.…”
Section: The Roles Of Trace Elementsmentioning
confidence: 99%
“…Primary Biliary Cholangitis (PBC) is a chronic cholestatic liver disease characterized by progressive destruction of the intrahepatic bile ducts, leading to cholestasis, portal inflammation, fibrosis and potentially cirrhosis and liver failure (1). Mononuclear phagocytes (MNPs) are myeloid immune cells comprised of monocytes, macrophages (MFs) and dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%